Imaginary Women, Imaginary Audience: Gender and Top 40 Radio in Montréal - Maki, Christine (Women in Radio: Unfiltered Voices from Canada, 2020)
Though they no longer call themselves Top 40, popular music radio stations remain present on the dial today, complete with loud, mostly male DJs, hoping to attract a mainly female audi ence. Using the talk on two Montréal music stations, which hire mainly male announcers who select music assumed to fit wom en’s tastes, Christine Maki examines the continuing perception that women’s voices aren’t low or authoritative enough and that emotional issues prevent them from presenting difficult news stories. Her conclusion: the overall medium remains relatively unchanged over the decades, despite massive evolution in the wider media landscape.

Venus On Venus: CKUT’s Women’s Collective Music Show Dishes on Feminist Radio - Leventhal, Anna; McInnis, Catherine; Wilson, Angela (Women in Radio: Unfiltered Voices from Canada, 2020)
Three volunteer hosts and programmers of a feminist music show at a campus-community radio station, Anna Leventhal, Catherine McInnis, and Angela Wilson, sat down in 2008 to chat about feminist radio. They discussed the concept of a feminist music show and the possibilities and limitations of female-only spaces; the “fem-con” concept that campus-community radio stations be mandated to play a certain amount of music by women, in the same way they are mandated by the CRTC to play Canadian content; the transformative social and political potential of community radio; and the inclusion of trans and gender-nonconforming voices on the show.